The Impact Of Recruitment, Training, And Discipline On Employee Performance: Examining Job Satisfaction As An Intervening Variable At Pt. Boga Indo Sejahtera Abadi (Pepper Lunch) Medan - Bawamenewi, Kornelius Aperianus (CV. SINAR HOWUHOWU, 2024)
This research investigates how employee performance significantly impacts organizational progress, emphasizing that strong performance fosters the achievement of company goals. The study aims to assess the effects of recruitment, training, and discipline on employee performance, with job satisfaction serving as an intervening variable at PT. Boga Indo Sejahtera Abadi (Pepper Lunch) in Medan. Data were collected through a questionnaire using a Likert scale, with a sample size of 98 respondents determined via the Slovin formula. Analysis was conducted using SmartPLS, evaluating convergent validity, discriminant validity, composite reliability, average variance extracted (AVE), collinearity statistics (VIF), path coefficients, coefficient determination, and hypothesis testing through Structural Equation Modeling (SEM). The findings indicate that recruitment, training, and discipline positively and significantly influence job satisfaction, as well as employee performance. Specifically, recruitment (T = 2.121, p < 0.05), training (T = 11.394, p < 0.05), and discipline (T = 6.064, p < 0.05) show significant effects on job satisfaction. Furthermore, all three factors also positively affect employee performance: recruitment (T = 2.516, p < 0.05), training (T = 10.168, p < 0.05), and discipline (T = 6.484, p < 0.05). Additionally, job satisfaction significantly enhances employee performance (T = 9.239, p < 0.05). Finally, recruitment (T = 2.175, p < 0.05), training (T = 6.813, p < 0.05), and discipline (T = 5.274, p < 0.05) positively influence performance through job satisfaction.